A hadith-based review of the validity of wuḍūʾ among Muslim women using waterproof cosmetics - Isnaini Lu'lu' Atim Muthoharoh (An-Nisa’ Journal of Gender Studies, 2023)
The increasing use of halal and contemporary cosmetic products among Muslim women has generated questions concerning waterproof cosmetics and their implications for the validity of wuḍūʾ in everyday religious practices. This study aims to analyze the relationship between wuḍūʾ and waterproof cosmetics from a hadith-based perspective, particularly concerning ritual validity and its implications for contemporary Muslim women’s religious practices. This study employs a qualitative literature review using thematic analysis, document-based data collection, and source triangulation to examine the validity of wuḍūʾ among users of waterproof cosmetics within a hadith and Islamic jurisprudence framework. The findings reveal three main results. First, wuḍūʾ encompasses spiritual, legal, and hygienic dimensions while intersecting with contemporary aesthetic practices, creating negotiation between ritual purity and personal appearance. Second, the cited hadiths emphasize that water must reach all body parts that must be washed; therefore, a cosmetic layer that prevents water from reaching the skin may affect the validity of wuḍūʾ. Third, waterproof cosmetics enhance makeup durability through water-resistant formulations but may have implications for skin health and ritual purification when their formulations create a physical barrier to water contact. The study concludes that the relationship between wuḍūʾ and waterproof cosmetics reflects tension between religious requirements and contemporary aesthetic needs. The relevant consideration is not merely whether a product is labeled “waterproof,” but whether its formulation prevents water from reaching the skin. This study contributes to understanding māniʿ (obstruction) in Islamic jurisprudence by connecting hadith-based principles with cosmetic science and provides practical considerations for Muslim women and beauty industry practitioners.